Effect of Nano-Zinc Foliar Spraying on Anatomical Characteristics of Soybean (Glycine max) Plants - Aljaf, Mouhannad Mahmood; Hasan, Susan Abdul-Raheem; AL-Hadeethi, Muazaz Azeez Hasan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In trendy farming, the use of Nano fertilizers is raising the productivity and strength of different crops by reducing the destructive effects of environmental changes. The current study is the first in Iraq to address anatomical characteristics and the Nanoscale effect on them. In the current study, the effect of Nano zinc oxide on the anatomy features of soybeans was tested. Concentrations of Nano zinc oxide were 0.75 and compared with control plants without spray. after doing the sections and examination, the results showed that the effect of Nano zinc oxide on the vascular bundle in the stem and midrib of leaf, also the length and width of stomata in leaf epidermis compared with control, as the stems of plants sprayed with Nano zinc were in an primary growth stage compared to the control treatment that were in secondary growth. Also, the diameter of bundles in control reached 297.3µ compared with the diameter of bundles treated with Nano zinc, which reached 116.2µ. On the other hand, the diameter of bundles in the midrib reached 135.7µ in the control and 148.1µ in the Nano zinc treatment, so the length and width of the stomata increased in the Nano zinc treatment.